2019
DOI: 10.3390/polym11030482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Superheated Steam Treatment on the Mechanical Properties and Dimensional Stability of PALF/PLA Biocomposite

Abstract: The effectiveness of superheated steam (SHS) as an alternative, eco-friendly treatment method to modify the surface of pineapple leaf fiber (PALF) for biocomposite applications was investigated. The aim of this treatment was to improve the interfacial adhesion between the fiber and the polymer. The treatment was carried out in an SHS oven for different temperatures (190–230 °C) and times (30–120 min). Biocomposites fabricated from SHS-treated PALFs and polylactic acid (PLA) at a weight ratio of 30:70 were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…As presented in Figure 4 , the XRD patterns of pure PLA showed a wide diffraction peak of approximately 2θ ≈ 18°. The PLA showed no characteristic peak and indicated that PLA has an amorphous structure [ 20 ]. The OPEFB also exhibits peaks at 2θ ≈ 16° and 2θ ≈ 24° indicating amorphous and crystalline regions [ 21 ], Cellulosic natural fibers contain both crystalline (ordered) and amorphous (disordered).…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Figure 4 , the XRD patterns of pure PLA showed a wide diffraction peak of approximately 2θ ≈ 18°. The PLA showed no characteristic peak and indicated that PLA has an amorphous structure [ 20 ]. The OPEFB also exhibits peaks at 2θ ≈ 16° and 2θ ≈ 24° indicating amorphous and crystalline regions [ 21 ], Cellulosic natural fibers contain both crystalline (ordered) and amorphous (disordered).…”
Section: Resultsmentioning
confidence: 99%
“…Although synthetic fibers provide high mechanical performance, they are unwelcomed due to environmental issues. Natural fibers supplant synthetic fibers as natural fibers offer the excellent properties including light weight, renewable resource, reasonable strength, superabundant, low density, non-irritating to skin and eye, inexpensive, bio-degradable, stiffness, non-toxic and eco-friendly [ 3 , 4 , 5 , 6 ]. The demand for light-weight natural fiber composites is increasing rapidly, especially in the automotive industry, which attributes weight reduction and therefore low fuel consumption [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we used PLA as a matrix and jute as a reinforcement to produce a complete biodegradable biocomposite. PLA is fermented from agricultural raw materials such as sugar, corn, beet, and potato in lactic acid [ 8 , 13 , 16 , 18 , 19 ] and has excellent mechanical properties [ 5 , 7 , 9 , 20 , 21 , 22 , 23 ], better biocompatibility [ 5 , 7 , 23 ], easily processable [ 7 , 23 ], transparency [ 20 ], and biodegradability [ 5 , 23 ]. Despite the properties, some modifications to PLA are required due to its brittleness, poor heat resistance, and low toughness properties [ 5 , 9 , 17 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of natural fiber composites has fascinated research attention in recent years because, in terms of weight reduction, fibers can replace conventional reinforcing materials [ 15 ]. PLA reinforced with pineapple leaf [ 16 ], kenaf [ 17 ], oil palm empty fruit bunch fiber (OPEFB) [ 18 ], and other natural fibers have been studied.…”
Section: Introductionmentioning
confidence: 99%